2011
DOI: 10.1002/ceat.201100259
|View full text |Cite
|
Sign up to set email alerts
|

Process Development for Antibody Purification from Tobacco by Protein A Affinity Chromatography

Abstract: Tobacco is possibly the most promising plant for plant‐made pharmaceuticals, e.g., antibodies, due to its high biomass yields and robust transformation technology. Protein A affinity chromatography is commonly used for antibody purification, however, direct application of tobacco extract to protein A chromatography columns may be problematic due to the nonspecific binding of native tobacco proteins (NTPs). Three different protein A resins, ProSep‐vA High Capacity, Ultra, and Ultra Plus, from Millipore were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Affinity resins from Millipore (ProSep®), Ultra Plus, vA Ultra and vA High Capacity were tested by Hey and Zhang . The resins were characterized based on the BC for antibodies and reusability on an incompressible porous glass matrix.…”
Section: Protein a Chromatographic Stationary Phasesmentioning
confidence: 99%
“…Affinity resins from Millipore (ProSep®), Ultra Plus, vA Ultra and vA High Capacity were tested by Hey and Zhang . The resins were characterized based on the BC for antibodies and reusability on an incompressible porous glass matrix.…”
Section: Protein a Chromatographic Stationary Phasesmentioning
confidence: 99%
“…Despite the aforementioned advantages of Nicotiana hosts, they do produce unusually higher levels of phenolics and alkaloids than other plant species. These compounds foul purification resins and are difficult to remove from the target RP in downstream processing, adding to production resources and costs [ 55 , 56 ]. This is especially problematic for RPs with pharmaceutical applications, as they need to be free of these plant compounds to meet regulations of the FDA.…”
Section: Agroinfiltration For Expression Of Recombinant Proteinsmentioning
confidence: 99%
“…Although antibodies can be purified well by affinity chromatography columns such as Protein A, studies showed that due to the presence of native compounds such as phenolics and alkaloids, direct loading of crude plant extract onto a Protein A media will result in column fouling and/or poor binding [1215]. The goal of this research is to develop a pre-chromatographic purification process to treat plant extracts so that the samples can be readily processed by various chromatographic methods for the purification of mAbs.…”
Section: Introductionmentioning
confidence: 99%